Deciphering and targeting host factors to counteract SARS-CoV-2 and coronavirus infections: insights from CRISPR approaches - Cui, Zhifen; Wang, Hongyan; Dong, Yizhou; Liu, Shan-Lu; Wang, Qianben (Frontiers in Genome Editing, 2023)
Severe respiratory syndrome coronavirus 2 (SARS-CoV-2) and other coronaviruses depend on host factors for the process of viral infection and replication. A better understanding of the dynamic interplay between viral pathogens and host cells, as well as identifying of virus-host dependencies, offers valuable insights into disease mechanisms and informs the development of effective therapeutic strategies against viral infections. This review delves into the key host factors that facilitate or hinder SARS-CoV-2 infection and replication, as identified by CRISPR/Cas9-based screening platforms. Furthermore, we explore CRISPR/Cas13-based gene therapy strategies aimed at targeting these host factors to inhibit viral infection, with the ultimate goal of eradicating SARS-CoV-2 and preventing and treating related coronaviruses for future outbreaks.